Humanitarian Intervention in a Multipolar World - Jesse Jones (Washington University Global Studies Law Review, 2015)
Humanitarian intervention is at a crossroads. In theory, humanitarian intervention has made significant advances in recent years; the “Responsibility to Protect” doctrine (or R2P) has achieved widespread adoption within a relatively short period of time. But in practice, humanitarian intervention appears to have reached a nadir. For Western nations, especially the United States, humanitarian goals have largely given way to security imperatives in the post-9/11 age. Since 2001, global instability has also risen, multiplying the list of possible candidates for humanitarian intervention. Yet in 2015, many conflicts exist around the world where humanitarian intervention has not yet been seriously discussed, let alone attempted. A growing acknowledgment of the failures of prior Western-backed military actions both for humanitarian purposes as well as for regime change has placed the burden of proof upon those favoring interventions to justify their positions as well as to set forth a clear “exit strategy.” For reasons of economy and policy, isolationism across both the left and the right of the political spectrum in the U.S. and Europe has also risen to levels not seen in decades. In the face of these pressures, the international community will need to adopt a new framework in order for humanitarian intervention not to become moribund. Part I of this Note will trace the history of humanitarian intervention from the 1980s to present day, focusing on how geopolitics has continually shaped humanitarian intervention. Part II will discuss the challenges of forming coalitions in favor of intervention within the emerging multipolar geopolitical world, whether through the U.N. or regional organizations. Part III summarizes and concludes with a prediction on the future of humanitarian intervention.
Keywords: humanitarian intervention; responsibility to protect; isolationism